2020
DOI: 10.1038/s41421-020-00225-2
|View full text |Cite
|
Sign up to set email alerts
|

The differential immune responses to COVID-19 in peripheral and lung revealed by single-cell RNA sequencing

Abstract: Understanding the mechanism that leads to immune dysfunction in severe coronavirus disease 2019 (COVID-19) is crucial for the development of effective treatment. Here, using single-cell RNA sequencing, we characterized the peripheral blood mononuclear cells (PBMCs) from uninfected controls and COVID-19 patients and cells in paired broncho-alveolar lavage fluid (BALF). We found a close association of decreased dendritic cells (DCs) and increased monocytes resembling myeloid-derived suppressor cells (MDSCs), whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
192
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(215 citation statements)
references
References 42 publications
19
192
3
1
Order By: Relevance
“…Additionally, increased IFN-γ promotes myeloid cell activation which is observed in the augmented percentage of inflammatory CD14+CD16+ monocytes in the LH group compared to healthy donors, supporting lymphopenia and virus persistence in these patients. This is supported by recent findings describing an increased gene expression in response to IFN-γ in mild and severe COVID-19 patients in peripheral myeloid cells (19) and the dysregulation in the balance of monocyte populations by the expansion of the monocyte subsets described in COVID-19 patients (22). Finally, we propose that long-lasting pulmonary damage observed in LH, is caused by a combination of factors including 1) longer virus persistence influenced by LH immune profile characterized by high IFN-γ and IL-2 levels inducing Th1 polarization which is ineffective with low CCL4-induced T cell recruitment, leading to an inflammatory myeloid cell activation; and 2) the immunopathological pulmonary effects consequence of this LH immune profile.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Additionally, increased IFN-γ promotes myeloid cell activation which is observed in the augmented percentage of inflammatory CD14+CD16+ monocytes in the LH group compared to healthy donors, supporting lymphopenia and virus persistence in these patients. This is supported by recent findings describing an increased gene expression in response to IFN-γ in mild and severe COVID-19 patients in peripheral myeloid cells (19) and the dysregulation in the balance of monocyte populations by the expansion of the monocyte subsets described in COVID-19 patients (22). Finally, we propose that long-lasting pulmonary damage observed in LH, is caused by a combination of factors including 1) longer virus persistence influenced by LH immune profile characterized by high IFN-γ and IL-2 levels inducing Th1 polarization which is ineffective with low CCL4-induced T cell recruitment, leading to an inflammatory myeloid cell activation; and 2) the immunopathological pulmonary effects consequence of this LH immune profile.…”
Section: Discussionsupporting
confidence: 78%
“…CCL4 signals through the receptor CCR5 to attract T cells to the site of inflammation and depending on the immune context, this molecule recruits differently activated T cells (17,18). Moreover, it was recently shown by single cell analysis a down regulation of CCL4 expression in peripheral myeloid cell compartments in patients with mild and severe COVID-19 (19). In LH, IFN-γ and IL-2 would create an immune context to induce Th1 polarization, but the low levels of CCL4 affect the recruitment of these cells impairing the antiviral response.…”
Section: Discussionmentioning
confidence: 99%
“…Even in recovery stages, early or late, COVID-19 patients were reported to have more CD14 ++ IL-1β + and IFN-activated monocytes in their peripheral blood than healthy controls 20 . Intriguingly, a population of myeloid-derived suppressor cells (MDSCs)-like monocytes, which correlated with lymphopenia and inflammation in the blood of severe COVID-19 patients, were found to be immune-paralyzed 21 . Besides, a study on the combination of COVID-19 and type II diabetes (T2D) 22 revealed that a morphological anomaly of increased monocyte size and monocytopenia restricted to classical CD14 high CD16 - monocytes was specifically associated with severe COVID-19 in patients with T2D requiring intensive care.…”
Section: Innate Immune Responsesmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted February 12, 2021. ; https://doi.org/10.1101/2021.02.12.430907 doi: bioRxiv preprint within an individual cell enables phenotypic analyses of a clonal population of lymphocytes and their dynamics [34][35][36] . scSeq of transcriptomes and immune repertoires in COVID-19 patients with severe symptoms has shown a high level of clonal expansion in specific T cell subsets (Th1, Th2, and Th17) and preferential germline gene usage in clonally expanded B cells 28,34,37 ; while a more recent study found a positive correlation between clonal expansion of effector-like CD8+ T cells and disease severity 38 .…”
Section: Introductionmentioning
confidence: 99%